IMPLEMENTASI METODE AHP DAN TOPSIS PADA SISTEM PENDUKUNG KEPUTUSAN CALON PENERIMA BEDAHRUMAH - Sari, Dian Megah (STKIP PGRI Sumatera Barat, 2020)
The objectives of this study were (i) to determine the system design for determining the recipient of house renovation (case study in North Bonde village) using AHP and TOPSIS, (ii) to determine the results of implementation using the AHP and TOPSIS methods in the decision support system for determining recipients of the house renovation program in Bonde village. north. This type of research is development research using the ADDIE model. The test subjects in this study were North Bonde village officials. Bonde village apparatus response data regarding the implementation of the AHP and TOPSIS methods in the Decision Support System for Prospective Recipients of Home Surgery is collected through a questionnaire. The data collected in the trial were then analyzed using qualitative analysis techniques. The results show that (i) the results of the application of the AHP and TOPSIS methods have succeeded in providing recommendations for determining prospective home renovation recipients, (ii) the results of testing the system with a blackbox show that the SPK has no defects or errors, which means that the system has fulfilled the functional requirements (iii) Accuracy testing was carried out using 105 data from North Bonde village families, which were used as testing data having an accuracy rate of 88% with a comparison of 12 invalid data and 93 valid data, (iv) in UAT testing (User Acceptance Test) resulted in 82% of users who stated that they strongly agreed with the existence of this system which can help determine prospective recipients of house renovations according to the criteria used